Efektivitas Pembagian Kewenangan Mahkamah Konstitusi Dan Pengadilan Tata Usaha Negara Dalam Penanganan Sengketa Pilkada Di Indonesia - Maemanah (Sawerigading Law Journal, 2025)
the authority to adjudicate disputes concerning election results (vote count disputes), while the State Administrative Court (Pengadilan Tata Usaha Negara/PTUN) has jurisdiction over procedural or administrative disputes related to State Administrative Decisions issued by election organizers. Therefore, this study aims to evaluate the effectiveness of the division of authority between the MK and PTUN in resolving regional head election (Pilkada) disputes in Indonesia, particularly after the enactment of Law Number 10 of 2016. This research employs legal research methods using a normative legal research approach, including statutory analysis and case study examination. The evaluation results indicate that the division of authority between MK and PTUN cannot yet be considered fully effective, as several critical issues remain. Overlapping authority frequently occurs, accompanied by differing interpretations between procedural disputes and result disputes, ultimately creating legal uncertainty. The current institutional design of judicial bodies handling Pilkada disputes contributes to ineffective dispute resolution and challenges the realization of electoral justice. The study recommends regulatory synchronization and reforms in administrative judicial mechanisms to ensure that PTUN decisions in Pilkada disputes are swift, final, and binding, similar to Constitutional Court decisions, thereby reducing uncertainty and jurisdictional overlap